Moral distress in carers for people with an intellectual disabilitywho died during the COVID-19 pandemic, a template analysisextending the Barlem and Ramos model of moral distress. - Mc Carron, Mary; Haigh, Margaret; Burke, Eilish; Wormald, Andrew (My University, 2023)
Background This article aims to understand moral distress in carers of people with an intellectual disability during the COVID-19 pandemic. Method Nine staff carers of seven people with an intellectual disability, who had been participants of the IDS-TILDA study in Ireland, who died during the COVID-19 pandemic participated in in-depth, semi-structured telephone interviews. Template analysis was used to analyze the interviews. Results Obstructions in performing their duties left carers feeling powerless and experiencing moral conflict distress, moral constraint distress and moral uncertainty distress. Most managed to connect to the moral dimension in their work through peer support, understanding they fulfilled the wishes of the deceased, and/or thinking about how they or others did the best they could for the person they were caring for. Conclusions This research demonstrates that while restrictions may have been effective in reducing the spread of COVID-19, they were potentially damaging to carer wellbeing.
PUBLISHED
Keywords: Moral distress; COVID-19; caring; moral resilience; moral residue; intellectual disability; Ageing; COVID 19; Intellectual Disability; Moral Distress